Gestão Baseada em Evidências e Os Limites do Gerencialismo na Gestão Municipal: um Estudo de Caso no Poder Local - Souza, Ariana Marchezi de (2021)
Since the mid-1990s, several initiatives for the generation of indicators have been adopted by cities that seek to measure aspects linked to urban systems. It turns out that the accumulation of data generated by these initiatives has fed huge databases, which ends up contributing to reduce the classic distance between academics who produce results of statistical analysis and professionals who consume them. These indicators support both the preparation of public planning and important management decisions. In the latter case, there is an approximation with an approach that specifically deals with the use of data as evidence for decision making, which is Evidence-Based Management (EBMgt). Thus, this thesis aimed to understand how public agents deal with different sources of evidence and use municipal indicators in the decision-making process of the municipal public power. To this end, a theoretical approach was adopted from the Public Administration that discusses the limits of managerialism in the public sector and the occurrence of multiple flows in decision making, which condition any proposal for the implementation of EBMgt in the public sphere, or Evidence-Based Policy (EBP). In methodological terms, a qualitative case study was delimited through semi-structured interviews, assessed through thematic content analysis. In this sense, from the data collected in the field research, it was found that there are different stages of structuring the EBP in the municipal public power, in addition to the simultaneous use of ex-ante evidence and ex-post evidence, which reveals the idea of the need to provide accounts of decisions already taken. Finally, the study determined that the transposition of EBMgt, a theoretical current feasible in the private sector, brings up clusters of limitations or filters peculiar to the public sector: political cycles, bargaining, intuition and experience of managers.